JENIS KESALAHAN YANG BIASA TERJADI DALAM KARANGAN SISWA BERBAHASA BAHASA JEPANG - Indrowaty, Sri Aju (Educate, 2014)
Sri Aju Indrowaty Unibraw – Malang Ayumirza9220@gmail.com Abstract The use of different languages raises various language errors, either consciously or unconsciously. The process of learning a second language cannot be separated from errors they may make. Making errors is a hallmark of learning. However, errors in language production is very disturbing in achieving the goal of attaining a good language. The types of errors made range from errors in listening (kiku), errors in speaking (hanasu), errors in reading (yomu), errors in writing (kaku). Using Japanese in writings, especially in an essay, often results in various errors. This article describes the grammatical errors that are often made by the students in their writings. This study at least find errors in morphological level, errors in phrasal level, and errors in syntactic level. Keywords: Errors, writing, type of errors Abstrak Pengunaan berbagai bahasa menimbulkan berbagai kesalahan berbahasa, baik disadari maupun tidak disadari. Proses pembelajaran bahasa kedua tidak terlepas dari adanya kesalahan. Kesalahan merupakan ciri dari pembelajaran. Namun demikian kesalahan dalam berbahasa sangat mengganggu dalam usaha tujuan pencapaian bahasa yang baik. Jenis kesalahan yang dilakukan bervariasi mulai dari kesalahan mendengarkan (kiku), kesalahan berbicara (hanasu), kesalahan membaca (yomu), kesalahan menulis (kaku). Penggunaan bahasa Jepang dalam penulisan, terutama dalam sebuah karangan sering menimbulkan berbagai kesalahan. Artikel ini menjelaskan tentang kesalahan-kesalahan gramatika yang sering dibuat oleh para siswa dalam karangan-karangan mereka. Penelitian ini setidaknya menemukan kesalahan dalam hal kesalahan morfologis, kesalahan frasa, dan kesalahan sintaksis. Kata kunci: Kesalahan, karangan, jenis kesalahan